Governing antimicrobial resistance in Norwegian livestock farming to 2050: a participatory strategy development approach - Helliwell, Richard; Boden, Lisa; Fuglestad, Eirik Magnus; Norström, Madelaine; Urdahl, Anne Margrete (Frontiers in Veterinary Science, 2025)
Antimicrobial resistance (AMR) is a wicked problem with long-term and unpredictable impacts on human and animal health. Understanding how to govern AMR long-term, amidst evolving social, political, economic, technological and environmental changes which will impact livestock production, animal health and AMR risks is therefore critical. The study used scenario planning as a methodology for envisioning plausible future challenges and thus identify possible strategic responses. The national context for this research was Norway, a stable, high-income country which has achieved low antibiotic use and low AMR prevalence in livestock farming through nearly 30 years of concerted industry and state actions. Working with Norwegian agricultural, animal and public health stakeholders, the scenario approach was motivated by the question of how to maintain existing governance capabilities and outcomes in an uncertain future. This is the first scenario planning study to explore stakeholder perceptions about important change drivers and strategies to manage uncertainties for AMR governance in the Norwegian livestock industry. Participants identified three critical drivers of change (state resource prioritisation of agriculture, trust in institutions, global geopolitical conditions) that would influence the development of Norwegian livestock farming, and public and private animal health and AMR governance capacity. The main threats were identified as erosion of trust impacting a culture of organisational collaboration on animal health, loss of capacity and solidarity in the context of declining farmers and veterinarians, and the tensions this produces between winners and losers. This was the basis for identifying several actions including the development of strong local networks of farmers, integrating veterinary and farm advisory services, utilising Ai and data technology to improve national animal health monitoring, and the need for sustaining the institutional and economic structures that are pre-conditions for work on AMR and animal health. These results highlight the importance of attending to these broader structural and institutional conditions that facilitate or hinder the adoption of biosecurity, antibiotic stewardship and preventive veterinary health measures as industry stakeholders and public authorities in Europe continue to grapple with AMR and antibiotic use in livestock farming.